Improving pre-service teachers’ AI competencies: a quasi experimental study - Han, Xiaotian (Frontiers in Psychology, 2025)
UNESCO’s sustainable development agenda underscores the critical need to equip pre-service teachers with artificial intelligence competencies, thereby enabling future generations to attain the global sustainable goal of quality education. This study aims to evaluate the perceptions concerning the AI competencies of pre-service teachers and investigates the influence of AI course helpfulness on the AI competency of pre-service teachers. A total of 79 pre-service teachers participated in AI courses, covering topics from foundational AI principles to interdisciplinary applications. Employing a quantitative correlational research design, the study assessed participants’ perceptions of the helpfulness of these AI courses, alongside their AI competencies, which were evaluated across six domains: AI awareness, basic AI knowledge, basic AI skills, problem-solving, AI teaching practice, and ethics and safety. These results show that the overall AI competency stood at a moderate level. Pre-service teachers have increased awareness of AI and ethics while they exhibit lower in problem-solving, basic AI skills, and AI teaching practice. Secondly, the findings showed that the role of well-structured AI courses enhancing the development of pre-service teachers’ AI-related capabilities is mostly supported. Further research is needed to determine the long-term effect of these AI training on classroom practices and teaching effectiveness.